Crash-energy absorbing structure and method of fabrication. - Ahmed Saad, Elsadig Mahdi; Mokhtar, Ahmed Samsuri; Taher, Siavash Talebi; Ahmadun, Fakhru'l-Razi; Abang Abdul Majid, Dayang Laila (2006)

(untitled)
The primary design goal crashworthiness in aerospace and automotive vehicles is to minimise the impact forces transmitted to the occupants during the crash events. In this study, an innovative lightweight composite energy-absorbing keel beam system has been developed to retrofit in aircraft and helicopter in order to improve their crashworthiness performance. The developed system consists of everting stringer and keel beam. The sub floor seat rails were designed as everting stringer to guide and control the failure mechanisms at precrush and post crush failure stages of composite keel beam webs and core. Polyurethane foam was employed to fill the core of the beam to eliminate any hypothesis of global buckling. The results shows that the crushing behaviour of the developed system is found to be sensitive to the revealed that the innovated system can be used for aircraft and helicopter and meet the requirements, together with substantial weight saving.